Graphene nanoplatelets as nanofillers in mesoporous silicon oxycarbide polymer derived ceramics. Issue 1 (December 2018) - Sujith, Ravindran; Chauhan, Pawan; Gangadhar, Jella; Maheshwari, Ankur
Abstract Understanding the role of graphene in the thermal stability and pore morphology of polymer derived silicon oxycarbide is crucial for electrochemical energy storage and hydrogen storage applications. Here in this work, we report the synthesis of graphene nanoplatelets dispersed silicon oxycarbide ceramics by the polymer to ceramic synthesis route. Samples containing graphene and without graphene are subjected to different pyrolysis conditions and are characterized using FT-IR, XPS, Raman spectroscopy, XRD, FE-SEM, HR-TEM, and BET. The results show that the graphene dispersed in the ceramic has undergone structural distortions upon pyrolysis and resulted in the formation of nanoclusters of graphene and turbostratic graphene. The XRD results confirm that with the incorporation of higher wt.% of GNP there is resistance to crystallization even at an exceedingly high pyrolysis temperature. The pores are bimodal in nature with specific surface area ranging between 22 and 70 m2 /g and are generatedin-situ during the polymer to ceramic conversion. Our study confirms that upon adjusting the graphene content it is possible to tune the structure and pore morphology of the polymer derived ceramics as per the requirements.